Agihan Kualitas Air Kali Surabaya Berdasarkan Perbedaan Penggunaan Lahan - Yulfiah Yulfiah; Ferry Suzantho; Maritha Nilam Kusuma (Fakultas Teknik, 2019)
Surabaya River is very beneficial to Surabaya people as its water becomes the main source of PDAM (Perusahaan Daerah Air Minum of Regional Water UtilityCompany). The existing indications on pollution in the flow of Surabaya River due to various activities at its riverbank must not be ignored. Therefore, a study on identifying the distribution of water quality of Surabaya River is required so as to be a reference for formulating control actions to river damage. Identification on water quality distribution was carried out based on the differences of land-use around the left and right sides of river. The research involved the variables of the qualities of river water and waste water thrown into the river, river characteris-tics, and land-use. The results of research demonstrated that the upstream water quality of Surabaya River was relatively better than the downstream. This statement was proven by the humans’ activities which were more intensively carried out at the downstream area. Numerous land-uses and great number of people living at the riverbank became the phenomena increasing pressures toward the decreasing quality of river water.